Biosignature Preservation and Detection in Mars Analog Environments - Hays, Lindsay E. (Astrobiology, 2017)
This review of material relevant to the Conference on Biosignature Preservation and Detection in Mars Analog Environments summarizes the meeting materials and discussions and is further expanded upon by detailed references to the published literature. From this diverse source material, there is a detailed discussion on the habitability and biosignature preservation potential of five primary analog environments: hydrothermal spring systems, subaqueous environments, subaerial environments, subsurface environments, and iron-rich systems. Within the context of exploring past habitable environments on Mars, challenges common to all of these key environments are laid out, followed by a focused discussion for each environment regarding challenges to orbital and ground-based observations and sample selection. This leads into a short section on how these challenges could influence our strategies and priorities for the astrobiological exploration of Mars. Finally, a listing of urgent needs and future research highlights key elements such as development of instrumentation as well as continued exploration into how Mars may have evolved differently from Earth and what that might mean for biosignature preservation and detection. Key Words: Biosignature preservation—Biosignature detection—Mars analog environments—Conference report—Astrobiological exploration. Astrobiology 17, 363–400.